Permainan Tradisional Sebagai Upaya Meningkatkan Karakter Disiplin dan Jujur Mahasiswa Pendidikan Guru Sekolah Dasar - Syahrul Jiwandono, Ilham (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Learning in the 21st century requires teachers to be creative in the learning process. Learning not only focuses on improving students 'cognitive abilities but also shapes students' characters. This study aims to illustrate the use of the game of talik in an effort to shape the character of discipline and honesty of students. The research approach uses a qualitative-descriptive approach by observing and exploring information directly in the field. Data collection using the method of documentation, observation, and structured interviews. Research location at the University of Mataram, Elementary School Teacher Education Study Program. Based on preliminary observations it is known that at that location still does not utilize traditional games optimally. Data collection techniques using interviews, observation, and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions or verification. The stages of the research are broadly divided into three parts, namely; 1) Stages of preparation / pre-field, 2) Stages of fieldwork, and 3) Stages of data analysis. The results showed: 1) Nowadays modern games are more widely used compared to traditional games. 2) The game of Swelling as one of the traditional games of the Sasak tribe has succeeded in becoming one of the media to form a disciplined and honest character of students.